A Rare Case of Plasma Cell Granuloma - Archana P. Kanteti; W. Patrick Kelsey; Ernesto Martinez Duarte (Hindawi Limited, 2020)
Plasma cell granulomas (PCGs) or inflammatory pseudotumors are nonneoplastic lesions that consist of predominantly antibody-secreting plasma cells and innate immune cells such as neutrophils, macrophages, and eosinophils. Unlike in multiple myeloma, the plasma cells are polyclonal and present in a spindly fibroblast-rich stromal background. These lesions mainly occur in the lungs; however, they can arise in other organs. PCGs from the gingiva are extremely rare, and a proper diagnosis is crucial to treat these patients further. These tumors have an increased number of plasma cells that are immunoreactive with CD138 and are polyclonal for kappa and lambda light chains, confirming these proliferations' nonneoplastic nature. Surgical resection with clear margins, when possible, is the primary choice of treatment. Radiation and anti-inflammatory steroid therapy are other therapeutic approaches. Critical and careful examination by a pathologist is necessary to rule out plasma cell neoplasms. Here, we report a rare occurrence of gingival PCG in an elderly male.